Arabidopsis VQ10 interacts with WRKY8 to modulate basal defense against Botrytis cinerea. Issue 10 (10th July 2018) - Chen, Junqiu; Wang, Houping; Li, Yang; Pan, Jinjing; Hu, Yanru; Yu, Diqiu
Abstract: Recent studies in Arabidopsis have revealed that some VQ motif‐containing proteins physically interact with WRKY transcription factors; however, their specific biological functions are still poorly understood. In this study, we confirmed the interaction between VQ10 and WRKY8, and show that VQ10 and WRKY8 formed a complex in the plant cell nucleus. Yeast two‐hybrid analysis showed that the middle region of WRKY8 and the VQ motif of VQ10 are critical for their interaction, and that this interaction promotes the DNA‐binding activity of WRKY8. Further investigation revealed that the VQ10 protein was exclusively localized in the nucleus, and VQ10 was predominantly expressed in siliques. VQ10 expression was strongly responsive to the necrotrophic fungal pathogen, Botrytis cinerea and defense‐related hormones. Phenotypic analysis showed that disruption of VQ10 increased mutant plants susceptibility to the fungal pathogen B. cinerea, whereas constitutive‐expression of VQ10 enhanced resistance to B. cinerea . Consistent with these findings, expression of the defense‐related PLANT DEFENSIN1.2 ( PDF1.2 ) gene was decreased in vq10 mutant plants, after B. cinerea infection, but increased in VQ10 ‐overexpressing transgenic plants. Taken together, our findings provide evidence that VQ10 physically interacts with WRKY8 and positively regulates plant basal resistance against the necrotrophic fungal pathogen B. cinerea . Abstract : VQ10 is a VQ motif‐containing protein, while WRKY8 is an important positive regulator of plant resistance against the necrotrophic fungal pathogen Botrytis cinerea . In this study, we demonstrated that VQ10 physically interacts with WRKY8 and activates its transcriptional activity, and the over‐expression of VQ10 enhances plant resistance to B. cinerea .